Intervention of Sensitivity Training in Human Relationship Management in a Information Technology Organization - Gupta, Seema Kumari (Journal of Advance Research in Computer Science & Engineering (ISSN 2456-3552), 2017)
The paper is on intervention of sensitivity training in Human Relationship Management, this is a powerful interference on self-awareness which gives an insight into all aspects of an individual relationship in their personal life as well as professional life. It is an orientation towards group dynamics process by which organizations educate themselves in order to achieve better problemsolving capabilities through healthier human relationship management. This in turn a significant positive change is achieved in the working cordial human relation between members. In this context, IT Organization (Confidential) categorical nominated their staff of various ranks for sensitivity training programme. The findings of 100 respondents are i) null hypothesis is accepted as p is greater than 0.05 which means that there is no association between gender and interpersonal relationship during the sensitivity training. ii) a) If p value < 0.05, reject null hypothesis. The impact of Sensitivity program on conflict management varies at different age groups and b) If p value > 0.05, accept null hypothesis. The impact of Sensitivity program on conflict management is the same at different age groups.